This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Solving the first equation gives:
α = 2 1 k π − β
Substituting this in the given sin leads to:
s i n ( 2 1 k π − β − β ) = s i n ( 2 1 k π − 2 β ) = c o s ( − 2 β ) = c o s ( 2 β )
I have used the identities s i n ( A + 2 1 k π ) = c o s ( A ) and c o s ( − A ) = c o s ( A )